Avaliação de Beauveria bassiana (Bals.) Vuill. e Metarhizium anisopliae (Metsch.) Sorok. para Controle de Sitophilus zeamais (Coleoptera: Curculionidae) - Potrich, Michele; Alves, Luis; Mertz, Natalia; Silva, Everton (BioAssay, 2009)
This research aimed to evaluate, under laboratory conditions, the entomopathogenic fungi Beauveria bassiana (Bals.) Vuill. and Metarhizium anisopliae (Metsch.) Sorok to control Sitophilus zeamais Mots. Bioassays were conducted to evaluate the pathogenicity of 16 isolates of B. bassiana and 2 isolates of M. anisopliae, based on virulence, vegetative growth and conidia production in Petri dishes and on rice and insect cadavers. All tested isolates were pathogenic to S. zeamais. The highest cumulative mortalities at 5th day were obtained with the isolates Unioeste 4, Unioeste 39 e Esalq 643 of B. bassiana. Regarding to the virulence, these three isolates did not differ among themselves. However, regarding to the colony average diameter, conidia production per colony and per cadaver, the isolate Esalq 643 was the most effective one. Regarding to rice conidia production, both Unioeste 4 and Esalq 643 isolates were equally productive. In general, the isolates Esalq 643 and Unioeste 4 were very effective with potential for exploiting in the microbial control of S. zeamais.